2022
DOI: 10.1111/cdoe.12792
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in spatial accessibility to public dental services relative to estimated need for oral health care among refugee populations in Victoria

Abstract: Objectives: To examine the spatial accessibility to public dental services (PDS) relative to the estimated oral health needs of refugee populations within the state of Victoria, Australia. Methods:The study employed enhanced two-step floating catchment area method to measure spatial accessibility to PDS by driving and public transit modes at statistical area level 2 (SA2). Principal component analysis of select census-derived socioeconomic variables specific to the refugee population was conducted to derive an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 38 publications
(75 reference statements)
0
6
0
Order By: Relevance
“…The perceptions of at least 3,561 different refugees and 259 rural health service providers and/or administrators were captured. Most studies looked at health access generally, although one study specifically examined the spatial accessibility of public dental services relative to the refugee population [ 21 ], while another reported on the major outcomes faced by mental health professionals working in the Rohingya humanitarian response [ 22 ]. Access to health services studied included all services, including local and governmental ones [ 20 , 23 31 ], primary, secondary, and hospital [ 13 , 22 , 30 , 32 ], mental [ 33 , 34 ], mobile [ 35 , 36 ], maternal and child health services [ 37 ], dental [ 21 ], online [ 25 , 38 , 39 ] and Médecins Sans Frontières [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The perceptions of at least 3,561 different refugees and 259 rural health service providers and/or administrators were captured. Most studies looked at health access generally, although one study specifically examined the spatial accessibility of public dental services relative to the refugee population [ 21 ], while another reported on the major outcomes faced by mental health professionals working in the Rohingya humanitarian response [ 22 ]. Access to health services studied included all services, including local and governmental ones [ 20 , 23 31 ], primary, secondary, and hospital [ 13 , 22 , 30 , 32 ], mental [ 33 , 34 ], mobile [ 35 , 36 ], maternal and child health services [ 37 ], dental [ 21 ], online [ 25 , 38 , 39 ] and Médecins Sans Frontières [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…This is not surprising; as noted in the Background healthcare can be difficult to access in rural areas for all members of rural communities. Factors that were recognised as impacting on access included the size of the rural or regional town or city, a lack of transportation, the judgemental attitudes of some doctors, and the availability of interpreters and health specialist services [ 13 , 21 , 22 , 30 , 31 , 33 , 35 , 37 , 40 ]. In Germany, Hahn et al [ 35 ] reported that the social security system can limit access to healthcare and specialists.…”
Section: Resultsmentioning
confidence: 99%
“…List of RHP sites were gathered from the Victorian Department of Health and were assigned to their respective SA2s based on their suburb and postcode in the postal address [ 19 ]. Spatial accessibility to PDS was calculated using the enhanced two-step floating catchment area method individually via road network (for driving mode including car or other motor vehicle) and public transit network (for various public transit modes including bus, tram, metro, or train), as detailed elsewhere [ 20 ]. The spatial accessibility index scores obtained from these calculations represent the ratio of full-time equivalent dental professionals to the population eligible for PDS within each SA2, weighted by the travel time between their respective locations via driving or public transit mode; these scores were used as continuous variables.…”
Section: Methodsmentioning
confidence: 99%
“…The perceptions of at least 3,561 different refugees and 259 rural health service providers and/or administrators were captured. Most studies looked at health access generally, although one study speci cally examined the spatial accessibility of public dental services relative to the refugee population [20], while another reported on the major outcomes faced by mental health professionals working in the Rohingya humanitarian response [21]. Access to health services studied included all services, including local and governmental ones [19,[22][23][24][25][26][27][28][29][30], primary, secondary, and hospital [13,21,29,31], mental [32,33], mobile [34,35], maternal and child health services [36], dental [20], online [24,37,38] and Médecins Sans Frontières [39].…”
Section: Methodsmentioning
confidence: 99%